2013
DOI: 10.1074/jbc.m112.410043
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 Suppresses Chondrocyte Proliferation in the Presence of Soluble α-Klotho both in Vitro and in Vivo

Abstract: Background:The role of elevated FGF23 in the development of growth retardation associated with X-linked hypophosphatemic rickets (XLH) remains elusive. Results: FGF23 suppresses chondrocyte proliferation in cooperation with soluble ␣-Klotho. Conclusion: Elevated FGF23 could have a causative role in the development of growth retardation in XLH. Significance: This may provide insights into the unrecognized function of FGF23 signaling in chondrocyte biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 40 publications
4
40
0
Order By: Relevance
“…In the current study, we identified Fgf23 as a strong transcriptional suppressor of TNAP in osteoblastic cells, acting through FGFR3 in a Klotho‐independent manner. In agreement with our findings, it was previously reported that Fgf23 binds to FGFR3 in vitro in chondrocytes . Hence, we hypothesize that Fgf23 secreted from osteocytes forms an autocrine/paracrine feedback loop in bone to indirectly regulate OPN secretion through TNAP.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we identified Fgf23 as a strong transcriptional suppressor of TNAP in osteoblastic cells, acting through FGFR3 in a Klotho‐independent manner. In agreement with our findings, it was previously reported that Fgf23 binds to FGFR3 in vitro in chondrocytes . Hence, we hypothesize that Fgf23 secreted from osteocytes forms an autocrine/paracrine feedback loop in bone to indirectly regulate OPN secretion through TNAP.…”
Section: Discussionsupporting
confidence: 93%
“…Although we found in UMR-106 cells that an AG490-mediated increase in Fgf23 mRNA was potently induced, correlation between Fgf23 mRNA and FGF23 protein remains to be determined. Finally, there is emerging evidence that FGF23 is produced in cells that comprise bone outside of osteoblasts/osteocytes, such as chondrocytes (Kawai et al, 2013) and in marrow (Xiao et al, 2013). Therefore, whether these other sites compensate for osteoblast/osteocyte FGF23 production is currently unknown, and gives rise to the idea that in the Hyp genetic background, multiple cell types may have to be targeted to fully affect circulating FGF23 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Fgf23 on cultured cells was often examined by the treatment of 10-100 ng/mL recombinant Fgf23, which is higher than its physiological serum levels. 17,18) Therefore, we also treated isolated macrophages with 100 ng/mL recombinant Fgf23. As LPS is known to stimulate cytokine expression in macrophages, we use LPS as a positive control.…”
Section: Fig 2 Expression Of Fgf23 In Immune Tissues and Cells (A) mentioning
confidence: 99%